Gregory of Nyssa: In Canticum Canticorum, Commentary and Supporting Studies. Proceedings of the 13th International Colloquium on Gregory of Nyssa (Rome, 17-20 September 2014). - Giulio Maspero; Miguel Brugarolas; Ilaria Vigorelli (Editors) (Vigiliae Christianae, Supplements, 2018)
Taken together, Gregory of Nyssa's XV Homilies In Canticum Canticorum are at the same time - as if in unison - a work of spiritual, exegetical, and theological doctrine. The wide spectrum of the themes present in them have prompted a great interest in this work, not only among scholars of patristics or theology, but also among those interested in biblical interpretation, ancient rhetoric or Christian mystical doctrine. These Proceedings present the results of the 13th International Colloquium on Gregory of Nyssa (Rome, 17-20 September 2014): a systematic commentary of Gregory's In Canticum from a broad perspective in the form of sixteen papers and a selection of fourteen short essays devoted to various issues that represent a valuable set of supporting studies.